First synthesis of podocarflavone A and its analogs and evaluation of their antimycobacterial potential against mycobacterium tuberculosis with the support of virtual screening - Puranik, Ninad V.; Swami, Sagar; Misar, Ashwini V.; Mamgain, Ritu; Gulawani, Swapnaja S.; Dhiman, Sarkar; Srivastava, Pratibha (Natural Product Research, 2022)
The first synthetic route developed for Podocarflavone A reported from Podocarpus macrophyllus and its analogs in 7 steps. Computational analysis for binding with the pantothenate kinase (3AVO) of Mycobacterium tuberculosis showed their docking score (ds) in the range of -8.9 to -9.3 Kcal/mol. MD simulations delineated the stability of the protein-ligand complexes in the TIP3P model. MMGBSA and MMPBSA values of 8d were -42.46 Kcal/mol and -14.58 Kcal/mol, respectively. Further in-vitro antitubercular screening of compounds 8a, 8d, and 8e against M. tuberculosis H37Ra using XRMA protocol exhibited promising antimycobacterial activity with IC50 values 21.82 mu g/mL, 15.55 mu g/mL, and 16.56 mu g/mL, respectively. Compounds 8a, 8d, and 8e showed antibacterial activity with IC50 values 41.56 mu g/mL, 24.72 mu g/mL, and 72.45 mu g/mL respectively against the Staphylococcus aureus. 8a and 8d showed inhibition with IC50 values 39.6 mu g/mL and 27.64 mu g/mL, respectively, against Bacillus subtilis. The present study could help in the further development of lead molecules against tuberculosis.
Keywords: and MMGBSA; antimycobacterial activity; docking; MD simulations; MMPBSA; Podocarflavone A synthesis

Design, synthesis, and in vitro biological evaluation of ROS-generating phenanthridin-trione-epoxide conjugates as agents against mycobacterium tuberculosis - Mamgain, Ritu; Swami, Sagar; Sarkar, Dhiman; Srivastava, Pratibha (ChemistrySelect, 2023)
Tuberculosis (TB) is one of the devasting infectious diseases and continues to spread among people despite having several specific drugs. Total eradication of TB is one of the shared interests of both the World Health Organization (WHO) and India globally. A library of antitubercular 6-((1-(aryl/heteroaryl)-1H-1,2,3-triazol-4-yl)methyl)oxireno[2,3-b] phenanthridine-5,7,9(6H,7aH,8aH)-trione (6 a-e) has been prepared in five steps including click chemistry and tested against active and dormant strains of Mycobacterium tuberculosis H37Ra using XRMA protocol. The result showed the inhibitory potential of 6 d IC50 at 0.74 & mu;g/mL concentration against active strain and at 0.9 & mu;g/mL against the dormant strain of Mtb. ROS generating ability of the compounds has been confirmed by luminol, H2O2, and glutathione assays. The molecular docking with the thioredoxin protein of Mtb showed a docking score of -9.6 Kcal/mol. To understand the mechanism with the thioredoxin protein of Mtb, the adduct formation of compounds with cystine was confirmed with HPLC. The involvement of lead molecules with existing drugs can be helpful in the eradication of tuberculosis.
Keywords: antimycobacterial agents; Computational docking; Cystine adduct; Epoxy-Phenanthridinone-triazoles; ROS generation